Kako se je Slovenija oskrbovala z lesom za kurjavo (drvmi) v obdobju 1945-1950 - Perko, Franc (Gozdarski vestnik, 2014)
The article presents diverse organizational forms and activities (staff offices for organization and control of firewood felling and preparation, youth work brigades, unionist brigades) for providing firewood to residents in towns and industrial centers in the period 1945 and 1950. These were the times when collective spirit was emphasized on every step. This contribution informs us about numerous obstacles and difficulties in implementing plans.
Keywords: forest; gozd; drva; brigade; sindikati; Slovenia; Slovenija; zgodovinski pregledi